Original metabolitotropic drug — elgacin: quantum-chemical properties and features of pharmacological action - Chekman, I.S.; Kazakova, O.O.; Dovgan, R. S.; Nagorna, A.A.; Belenichev, I.F.; Gorchakova, N.A.; Bukhtiyarova, N.V.; Syrovaya, G.O.; Zahorodnyi , M.I. (Reports of the National Academy of Sciences of Ukraine, 2018)
The density functional theory and the IEF PCM solvation model are used to investigate the electronic and energy properties of an elgacin molecule. A quite significant positive charge on protons of hydroxyl groups determines its pronounced antioxidant activity. The negative value of the lowest unoccupied molecular orbital energy determines the electrophilic properties of the molecule. The variety of functional groups evidences about a possibility of its interaction with polar and nonpolar structures of biomembranes.